2015
DOI: 10.1016/j.neubiorev.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

The prosocial effects of 3,4-methylenedioxymethamphetamine (MDMA): Controlled studies in humans and laboratory animals

Abstract: Users of ±3,4-Methylenedioxymethamphetamine (MDMA; ‘ecstasy’) report prosocial effects such as sociability and empathy. Supporting these apparently unique social effects, data from controlled laboratory studies indicate that MDMA alters social feelings, information processing, and behavior in humans, and social behavior in rodents. Here, we review this growing body of evidence. In rodents, MDMA increases passive prosocial behavior (adjacent lying) and social reward while decreasing aggression, effects that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 96 publications
(242 reference statements)
2
127
0
1
Order By: Relevance
“…Previous placebo-controlled experimental studies have also shown that a single dose of MDMA can increase sociability and different aspects of empathy (Kamilar-Britt and Bedi, 2015). Behavioral tasks of empathy measure an individual’s response to faces showing a positive or negative emotional expression.…”
Section: Introductionmentioning
confidence: 94%
“…Previous placebo-controlled experimental studies have also shown that a single dose of MDMA can increase sociability and different aspects of empathy (Kamilar-Britt and Bedi, 2015). Behavioral tasks of empathy measure an individual’s response to faces showing a positive or negative emotional expression.…”
Section: Introductionmentioning
confidence: 94%
“…Multiple studies of social behavior in rodents after MDMA exposure have reported significant prosocial effects (Kamilar-Britt & Bedi, 2015), including decreased aggressive behavior and increased social interaction (Morley & McGregor, 2000). Some of these effects have been shown to be attenuated by pre-treatment with an oxytocin receptor antagonist (Thompson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…First, many studies have demonstrated that MDMA produces positive, “prosocial” effects, such as the facilitation of social interaction in humans and other species (Bedi et al 2010; Hysek et al 2013; Kamilar-Britt and Bedi 2015; Kirkpatrick et al 2015; Thompson et al 2007). We reasoned that these prosocial effects might reduce the negative emotional impact of the public speaking task.…”
Section: Discussionmentioning
confidence: 99%
“…Although the drug may be used to cope with the psychological stress of these settings, it has been suggested that MDMA may actually increase the physiological stress response in these contexts (Parrott 2009). Several studies have investigated the effects of MDMA on responses to threatening social stimuli under controlled laboratory conditions (for reviews, see Kamilar-Britt and Bedi 2015; Bershad et al 2016). These studies show that MDMA reduces reactivity to faces expressing negative emotions.…”
Section: Introductionmentioning
confidence: 99%